Stability and Degradation Pathways of Different Psychoactive Drugs in Neat and in Buffered Oral Fluid. Issue 6 (5th February 2020) - Marchei, Emilia; Malaca, Sara; Graziano, Silvia; Gottardi, Massimo; Pichini, Simona; Busardò, Francesco Paolo
Abstract: Sampling and drug stability in oral fluid (OF) are crucial factors when interpreting forensic toxicological analysis, mainly because samples may not be analyzed immediately after collection, potentially altering drug concentrations. Therefore, the stability of some common drugs of abuse (morphine, codeine, 6-monoacetylmorphine, cocaine, benzoylecgonine, Δ9-tetrahydrocannabinol, cannabidiol, amphetamine, 3, 4-methylenedioxymethamphetamine, ketamine) and the more commonly consumed new psychoactive substances in our environment (mephedrone, and N-(adamantan-1-yl)-1-(5-fluoropentyl)-1H-indazole-3-carboxamide 5F-AKB48 also known as 5F-APINACA) was investigated in an OF pool for the presence and absence of M3 Reagent Buffer® up to 1 year of storage. Fortified OF samples were stored at three different temperatures (room temperature, 4 and −20°C) to determine the best storage conditions over time. Control fortified OF samples were stored at −80°C for reference purposes. Compounds with concentration changes within ±15% of initial value were considered stable. The drugs were significantly more stable in M3 Reagent Buffer® than in neat OF samples in all storage conditions. All analytes were stable for 1 year at 4°C and −20°C in M3 Reagent Buffer®. Drugs stability in OF varied depending on the analyte, the presence of a stabilizer, the storage duration and temperature. When immediate sample analysis is not possible, we suggest to store OF samples at 4 or −20°C and test them within 2 weeks. Alternatively, OF samples may be stored at 4 or −20°C with M3 Reagent Buffer® to be tested within 1 year.